2015
DOI: 10.1371/journal.pone.0138362
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Primary School Non-Enrollment and Absenteeism: Results from a Retrospective, Convergent Mixed Methods, Cohort Study in Rural Western Kenya

Abstract: BackgroundEducation is a key element in the socioeconomic development required to improve quality of life in Kenya. Despite the introduction of free primary education, primary school enrollment and attendance levels remain low. Drawing on qualitative and quantitative data, this study explores the determinants of non-enrollment and absenteeism in rural western Kenya and potential mitigation strategies to address these issues.MethodsThe study was conducted in Bwaliro village in rural western Kenya. A random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
(49 reference statements)
0
17
0
2
Order By: Relevance
“…School attendance is known to be sensitive to contextual changes both at the school level, such as the introduction of a school feeding programme, or at the local environmental level, such as weather patterns and their effect on the local harvest 6. Such changes are unavoidable and though monitored and broadly accounted for wherever possible, they may have exerted unobserved heterogeneity on the primary outcome of attendance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…School attendance is known to be sensitive to contextual changes both at the school level, such as the introduction of a school feeding programme, or at the local environmental level, such as weather patterns and their effect on the local harvest 6. Such changes are unavoidable and though monitored and broadly accounted for wherever possible, they may have exerted unobserved heterogeneity on the primary outcome of attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Although measured at baseline and included in the initial study stratification, the extent of school-feeding programmes changed throughout the study period, and these are known to influence enrolment and attendance 48–50. Furthermore, information on whether the children were orphans or vulnerable children, or involved in child labour, both risk factors previously shown to be associated with attendance,6 51 were not collected. However, due to the randomised design, such changes and risk factors are likely to be similar across groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, education, one of the basic human rights, is regarded by the World Bank (1993) as the catalyst of human development and economic growth (cited by Okumu, Nakajjo & Isoke, 2008) and by researchers as a requirement for socio-economic development and life quality (King, N., Dewey, C., & Borish, D., 2015). On the other hand, the study results indicate that family's educational and income level, the indicator of socio-economic status, is the strongest determinant of school success and attendance (Rumburger, 2001:14).…”
Section: Resultsmentioning
confidence: 99%
“…However, the impact of health factors on educational outcomes for schoolchildren is widely recognized, including by governments [ 5 ]. Previous research on the effect of malaria on children’s education showed that malaria is the leading cause of school absenteeism [ 6 , 7 ] and asymptomatic malaria was likely to affect school performance [ 8 ]. In addition, malaria remains the biggest killer among school-aged children, causing 50 % of deaths in this age group in sub-Saharan Africa [ 9 ].…”
Section: Introductionmentioning
confidence: 99%